The viability of urban agriculture in reducing food insecurity in Gweru, Mkoba 19 surburb. - Ziwenga, Francis T. (Midlands State University, 2017)
The paper examined the viability of urban agriculture in reducing food insecurity in Gweru, Mkoba 19 suburb. The study aimed to ascertain the prevalence of urban agriculture, its effects on food security and the challenges to its practice. A questionnaire was administered to 107 household heads engaged in urban agriculture. The study revealed that urban agriculture had been widely adopted by the households in the suburb. It provided a variety of foods to households such a meat, vegetables and the staple mealie-meal thereby making food available and accessible to the households, it also provided employment and income to the households. The challenges to the practice were the shortage of water, land, and lack of technical and institutional support, poor laws on urban agriculture, poor market linkages, the consumption of crops by livestock and the scarcity funds which resulted in poor production. The study recommended that the government should come up with an explicit broad policy on urban agriculture and should also empower local governments to make by-laws that support urban agriculture as a legitimate economic activity. Measures were also suggested to address the challenges to urban agriculture in Mkoba 19.